The efficacy of cognitive stimulation, cognitive training, and cognitive rehabilitation for people living with dementia: a systematic review and meta-analysis - Alice Paggetti; Ylenia Druda; Francesco Sciancalepore; Francesco Della Gatta; Antonio Ancidoni; Nicoletta Locuratolo; Paola Piscopo; Luca Vignatelli; Luciano Sagliocca; Antonio Guaita; Piero Secreto; Andrea Stracciari; et al. (GeroScience, 2024)
Cognition-oriented treatments (COTs) are a group of non-pharmacological treatments aimed at maintaining or improving cognitive functioning. Specific recommendations on the use of these interventions in people living with dementia (PLwD) are included in the Italian Guideline on the Diagnosis and Treatment of Dementia and Mild Cognitive Impairment, developed by the Italian National Institute of Health. This systematic review and meta-analysis, based on the GRADE methodology, is part of the guideline. Considered outcomes included the cognitive functions, quality of life, and functional abilities of PLwD, taking into account disease severity, modality and system of delivery, and form of the intervention. The effectiveness of these interventions on caregivers’ outcomes was also assessed. Both group and individual cognitive stimulation were reported as effective in supporting cognitive functions in PLwD at any degree of severity. Individual cognitive training and group cognitive training were reported as effective in improving global cognitive functions in people with mild dementia. Cognitive rehabilitation appeared to be effective only in improving the functional abilities of people with mild dementia. Cognitive rehabilitation appeared to be the most effective in improving caregivers’ outcomes, with results suggesting a reduction in care burden. The observed differences in the effectiveness of these interventions in people with different disease severity can be explained by the intrinsic characteristics of each intervention. Despite the large number of available studies, a high clinical, statistical, and methodological heterogeneity was observed. More methodologically rigorous studies are needed to clarify the effectiveness of each protocol and modality of intervention.

Seed morphological variation in four closely related Linaria species (Plantaginaceae) endemic to the Tyrrhenian area - M. Sarigu; M. Ucchesu; A. Carta; L. Peruzzi; G. Bacchetta (Plant Biosystems, 2024)

Corrigendum to “Biochar soil amendment as carbon farming practice in a Mediterranean environment” [Geoderma Regional, 33, 2013, e00634] - I. Nogués; V. Mazzurco Miritana; L. Passatore; M. Zacchini; E. Peruzzi; S. Carloni; F. Pietrini; R. Marabottini; T. Chiti; L. Massaccesi; S. Marinari (Geoderma Regional, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Biochar soil amendment as carbon farming practice in a Mediterranean environment - I. Nogués; V. Mazzurco Miritana; L. Passatore; M. Zacchini; E. Peruzzi; S. Carloni; F. Pietrini; R. Marabottini; T. Chiti; L. Massaccesi; S. Marinari (Geoderma Regional, 2023)

DNA barcoding approach fails to discriminate Central European bladderworts (Utricularia, Lentibulariaceae), but provides insights concerning their evolution - G. Astuti; G. Petroni; L. Adamec; V. F. O. Miranda; L. Peruzzi (Plant Biosystems, 2020)

Narrow endemic species Bellevalia webbiana shows significant intraspecific variation in tertiary CSR strategy - G. Astuti; D. Ciccarelli; F. Roma-Marzio; A. Trinco; L. Peruzzi (Plant Biosystems, 2019)

Are shoots of diagnostic value in Central European bladderworts ( Utricularia L., Lentibulariaceae)? - G. Astuti; L. Peruzzi (Plant Biosystems, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

Floristic inventories and collaborative approaches: a new era for checklists and floras? - L. Peruzzi (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Effects of UV radiation and rainfall reduction on leaf and soil parameters related to C and N cycles of a Mediterranean shrubland before and after a controlled fire - L. Díaz-Guerra; D. Verdaguer; M. Gispert; G. Pardini; J. Font; J. A. González; E. Peruzzi; G. Masciandaro; L. Llorens (Plant and Soil, 2018)

Phylogenetic relationships among tetraploid species of Bellevalia (Asparagaceae) endemic to south-central Mediterranean - G. Astuti; S. Brullo; G. Domina; R. El Mokni; T. Giordani; L. Peruzzi (Plant Biosystems, 2017)

Chromosome diversity and evolution in Allium (Allioideae, Amaryllidaceae) - L. Peruzzi; A. Carta; F. Altinordu (Plant Biosystems, 2017)

The avoidance of self-interference in the Tuscan endemic spring geophyte Crocus etruscus Parl. (Iridaceae) - A. Carta; S. Campigli; L. Peruzzi; G. Bedini (Plant Biosystems, 2016)

A new infrafamilial taxonomic setting for Liliaceae, with a key to genera and tribes - L. Peruzzi (Plant Biosystems, 2016)

All in an afternoon: mixed breeding system in one-day lasting flowers of Hypericum elodes L. (Hypericaceae) - A. Carta; L. Savio; G. Bedini; L. Peruzzi; A. Fisogni; M. Galloni (Plant Biosystems, 2016)

Wikiplantbase #Toscana, breaking the dormancy of floristic data - G. Bedini; B. Pierini; F. Roma-Marzio; K.F. Caparelli; G. Bonari; D. Dolci; G. Gestri; M. D'Antraccoli; L. Peruzzi (Plant Biosystems, 2016)

Three new hybrids of Ophioglossum (Ophioglossaceae) from Monte Pisano, Tuscany (Central Italy) - L. Peruzzi; B. Pierini; S. Magrini; A. Andreucci; D. Marchetti; R. Viane (Plant Biosystems, 2015)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

“ x ” is not a bias, but a number with real biological significance - L. Peruzzi (Plant Biosystems, 2013)

Phylogenetic relationships of Italian Bellevalia species ( Asparagaceae ), inferred from morphology, karyology and molecular systematics - A. Borzatti Von Loewenstern; T. Giordani; G. Astuti; A. Andreucci; L. Peruzzi (Plant Biosystems, 2013)

A new butterwort species ( Pinguicula , Lentibulariaceae) from Northern Apennine (Italy) - L. Peruzzi; G. Gestri (Plant Biosystems, 2013)

Karyological knowledge of the Italian vascular flora as inferred by the analysis of “Chrobase.it” - G. Bedini; F. Garbari; L. Peruzzi (Plant Biosystems, 2012)

Cytogenetic characterization of endemics: past and future - Sonja Siljak-Yakovlev; L. Peruzzi (Plant Biosystems, 2012)

New trends in plant cytogenetics and cytoembryology: Dedicated to the memory of Emilio Battaglia - L. Peruzzi; F. Garbari; G. Bedini (Plant Biosystems, 2012)

Parallelism in the oxygen transport system of the lake whitefish: the role of physiological divergence in ecological speciation - MELISSA L. EVANS; KIM PRÆBEL; STEFANO PERUZZI; LOUIS BERNATCHEZ (Molecular Ecology, 2012)
In North America, populations of lake whitefish ( Coregonus clupeaformis ) have evolved sympatric ‘dwarf’ and ‘normal’ ecotypes that are associated with distinct trophic niches within lakes. Trophic specialization should place diverging physiological demands on individuals, and thus, genes and phenotypes associated with energy production represent ideal candidates for studies of adaptation. Here, we test for the parallel divergence of traits involved in oxygen transport in dwarf and normal lake whitefish from Québec, Canada and Maine, USA. We observed significant differences in red blood cell morphology between the ecotypes. Specifically, dwarfs exhibited larger nuclei and a higher nucleus area/total cell area than normal whitefish in all of the lakes examined. In addition, isoelectric focusing gels revealed variation in the haemoglobin protein components found in whitefish. Dwarf and normal whitefish exhibited a similar number of protein components, but the composition of these components differed, with dwarf whitefish bearing a greater proportion of cathodic components compared to the normals. Furthermore, dwarf whitefish showed significant haemoglobin gene upregulation in the brain compared with the levels shown in normals. Together, our results indicate that metabolic traits involved in oxygen transport differ between the whitefish ecotypes and the strong parallel patterns of divergence observed across lakes implicates ecologically driven selection pressures. We discuss the function of these traits in relation to the differing trophic niches occupied by the whitefish and the potential contributions of trait plasticity and genetic divergence to energetic adaptation.

Does Plantago brutia Ten. (Plantaginaceae) merit specific rank? Insights from nrDNA and cpDNA data - A. M. Palermo; A. De Vita; L. Peruzzi; D. Gargano; L. Bernardo; A. Musacchio (Plant Biosystems, 2010)

Gagea bohemica (Liliaceae), a highly variable monotypic species within Gagea sect. Didymobulbos - A. Peterson; D. Harpke; L. Peruzzi; J.‐M. Tison; H. John; J. Peterson (Plant Biosystems, 2010)

A biometric study of Fritillaria montana Hoppe ex W.D.J. Koch s.l. (Liliaceae) shows a single polymorphic species, with no infraspecific taxa - F. Bartolucci; K. F. Caparelli; L. Peruzzi (Plant Biosystems, 2009)

Phylogenetic relationships of Gagea Salisb. (Liliaceae) in Italy, inferred from molecular and morphological data matrices - L. Peruzzi; A. Peterson; J.-M. Tison; J. Peterson (Plant Systematics and Evolution, 2008)

Hybridity as a main evolutionary force in the genus Gagea Salisb. (Liliaceae) - L. Peruzzi (Plant Biosystems, 2008)

A comparative analysis of embryo-sac development in three closely-related Gagea species (Liliaceae), with some considerations on their reproductive strategies - K. F. Caparelli; L. Peruzzi; G. Cesca (Plant Biosystems, 2006)

p73 modulates HIV-1 Tat transcriptional and apoptotic activities in human astrocytes - M. Saunders; M. B. Eldeen; L. Del Valle; K. Reiss; F. Peruzzi; G. Mameli; B. B. Gelman; K. Khalili; S. Amini; B. E. Sawaya (Apoptosis, 2005)